2010
DOI: 10.3390/ma3021172
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Sublimation Pressures of Some Ruthenocene Compounds

Abstract: We set out to study the use of a series of ruthenocenes as possible and promising sources for ruthenium and/or ruthenium oxide film formation.The thermal stability of a series of ruthenocenes, including (η5-C5H4R)(η5-C5H4R´)Ru (1), R = R´ = H (3), R = H, R´ = CH2NMe2 (5), R = H, R´= C(O)Me (6), R = R´ = C(O)Me (7), R = H, R´ = C(O)(CH2)3CO2H (8), R = H, R´ = C(O)(CH2)2CO2H (9), R = H, R´ = C(O)(CH2)3CO2Me (10), R = H, R´= C(O)(CH2)2CO2Me (11), R = R´ = SiMe3), (η5-C4H3O-2,4-Me2)2Ru (2), and (η5-C5H5-2,4-Me2)2R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…However, above 300 °C, a great weight loss of PMAERu was observed. The integration of ruthenocene moiety into polymeric framework made sublimation unlikely, but only occurred when the polymeric framework was decomposed. , According to the DSC trace (Figure B), the homopolymer PMAERu shows glass transition temperature at T g = 66 °C, which is similar to reported ferrocene-containing polymer and cobaltocenium-containing polymers with similar polymeric framework …”
Section: Resultssupporting
confidence: 62%
“…However, above 300 °C, a great weight loss of PMAERu was observed. The integration of ruthenocene moiety into polymeric framework made sublimation unlikely, but only occurred when the polymeric framework was decomposed. , According to the DSC trace (Figure B), the homopolymer PMAERu shows glass transition temperature at T g = 66 °C, which is similar to reported ferrocene-containing polymer and cobaltocenium-containing polymers with similar polymeric framework …”
Section: Resultssupporting
confidence: 62%
“…However, to understand the quantitative differences in the reactivity of such ruthenocenes at least a theoretical investigation is required by optimizing the structures and calculating the electron density on each molecule. The physical properties of such molecules reported by Siddiqi et al 128 could be taken into consideration to correlate their physical properties with the localization of electron density on ruthenium atom or on the molecular skeleton as a whole. It is concluded that 17-26 are most thermally stable molecule good volatility for CVD application.…”
Section: (B) Organometallic Ruthenium Derivativesmentioning
confidence: 99%
“…In this Coatings 2024, 14, 33 2 of 9 case, ALD is a type of chemical vapor deposition (CVD) technique with monolayer-bymonolayer growth of angstrom resolution [23][24][25]. This deposition technique is widely used in the microelectronics industry [26][27][28]. Also, ALD is used for the modification of various surfaces and for the protection and encapsulation of nanostructures [29][30][31].…”
Section: Introductionmentioning
confidence: 99%